PERANAN SISTEM HUKUM DALAM PEMBENTUKAN TATANAN KEHIDUPAN MASYARAKAT INDONESIA - Muhammad Farhan Bramudia; Andika Firansah; Muhammad Bimo Nugroho; Tubagus Mido Hossam (Jurnal Riset Multidisiplin Edukasi, 2025)
The legal system plays an essential role in the formation, regulation, and maintenance of social stability in Indonesia. Through various norms, provisions, and law enforcement agencies, the state strives to create social order while minimizing the potential for conflict. This paper examines how the legal system contributes to shaping societal behavior, maintaining public order, and promoting social justice. The analysis shows that the effectiveness of the legal system is determined not only by the quality of its regulations but also by the consistency of their implementation and the level of public legal awareness.